Efficacy of rituximab in primary Sjögren's syndrome with peripheral nervous system involvement: results from the AIR registry. Issue 1 (16th September 2011) - Mekinian, A; Ravaud, P; Hatron, P Y; Larroche, C; Leone, J; Gombert, B; Hamidou, M; Cantagrel, A; Marcelli, C; Rist, S; Breban, M; Launay, D; et al.
Abstract : Objective: To evaluate rituximab (RTX) in primary Sjögren's syndrome (pSS) with peripheral nervous system (PNS) involvement. Methods: Patients with pSS and PNS involvement who were included in the French AIR registry were analysed. Results: 17 patients (age 60 years (44–78 years); 14 were female) were analysed. Neurological improvement was noted in 11 patients (65%) at 3 months. Rankin scale decreased from 3 (1–5) to 2 (1–5), 2 (1–5) and 2 (1–6) after 3, 6 and 9 months (p=0.02). European Sjögren's Syndrome Disease Activity Index decreased from 18 (10–44) to 11 (5–20), 11 (5–29) and 12 (5–30) after 3, 6 and 9 months (p<0.05). RTX was effective in neurological involvement in 9/10 patients with vasculitis or cryoglobulinaemia (90%) (group 1) at 3 months and in 2/7 cases (29%) without cryoglobulinaemia and vasculitis (p=0.03). Rankin and European Sjögren's Syndrome Disease Activity Index scales decreased significantly in group 1. Conclusion: RTX seems effective in cryoglobulinaemia or vasculitis-related PNS involvement in pSS.